The Measurement of Precarious Work and Market Conditions: Insights from the COVID-19 Disruption on Sample Selection. Issue 1 (February 2023) - Alon, Sigal
The precarious work construct combines employment instability and employment-contingent outcomes. Yet, I argue that confining the scope of the investigation to employed individuals creates a sample selection that disguises the heterogeneous nature of employment instability. The COVID-19 skyrocketing unemployment rate provides both a compelling motivation and a unique opportunity to revisit the construct of precarious work. Using pre-COVID and COVID-19 era data of the working-age population in Israel, the results demonstrate that by pushing less stable individuals out of employment, the COVID-19 recession strengthened the negative relationship between volatility and employment opportunities and accentuated sample selection. Because the selection into employment was not random, this introduces a bias into the measurement of precarious work, one that is more severe during a recession than in a full-employment market. The discussion highlights the broader significance of this lacuna and suggests a way to hone the conceptualization and operationalization of the precarious work construct.